Machine learning and medical engineering for cardiovascular health and intravascular imaging and computer assisted stenting : first International Workshop, MLMECH 2019, and 8th Joint International Workshop, CVII-STENT 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13, 2019, Proceedings /: first International Workshop, MLMECH 2019, and 8th Joint International Workshop, CVII-STENT 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13, 2019, Proceedings. (2019) - Unknown
No abstract available